Physical activity of pregnant women in the light of scientific research - a review of the literature - Sass, Anna; Mączka, Martyna (Journal of Education, Health and Sport, 2017)
Introduction: Physical activity during pregnancy is very important due to health benefits for women and fetus. Undoubtedly, physical activity should be adapted to the current psychophysical abilities of pregnant women. During that time, the physical effort should be taken by appropriate intensity, also the forms of physical activity should be general aimed in current pregnancy state. Undoubtedly the simplest form of physical activity for pregnant women is walk, as well as swimming, gymnastics, yoga and pilates. Exercises should have wide impact on her body and muscles. The aim of the study is to identify the physical activity of pregnant women in available scientific publications. Further goal is the assessment of the knowledge about the physical activity of pregnant women based on the current review of the literature. Research Methods: The following databases and scientific browsers were used and tracked for the purpose of the research objective: Pub Med, Retina Medical Search, Medline Plus, Europe PMC, POPLINE, Google Scholar. During searching for a results the keywords phrases were written in English: physical activity in pregnancy, pregnancy exercises, fitness, yoga, pilates, swimming and pelvic floor exercises during pregnancy. Conclusions: The current researches among the population of pregnant women are methodologically differentiated and not coherent in the subject. The implication of unexplored issues about pregnant women is the differentiation in directions of researches about the physical activity of pregnant women. It seems that is important to design and program an prospective research by using objective techniques to explore the pregnant women’s behavior, lifestyle and physical activity.